Hubungan antara Motivasi Belajar dengan Hasil Belajar Siswa dalam Pembelajaran IPA di Sekolah Dasar - Utami, Mita Midra; Desyandri, Desyandri (Universitas Negeri Padang, 2021)
This study aims to determine whether or not there is a relationship between learning motivation and student learning outcomes in natural science learning in class V of Guguk Panjang Barat Elementary School, West Bukittinggi.This type of research is quantitative research with a correlation research design. The sample of this study consisted of 21 fifth grade students of Guguk Panjang Barat Gugus I Elementary School, Bukittinggi City. Based on the analysis of the data that has been done, the results of the study show that there is a significant relationship between learning motivation and student learning outcomes in science learning in class V of the Guguk Panjang Barat Public Elementary School in West Bukittinggi.This is evidenced by the value of r count = 0.5587> rtable = 0.433 at a significance level of 0.05 (5%) which means Ho is rejected and Ha is accepted, so the hypothesis says